Female Adolescents in attitudes and side effects of consuming iron supplements - Sety, La Ode Muhamad; Syarifuddin, Yuliana; Tina, Lymbran; Majid, Ruslan (Al-Sihah: The Public Health Science Journal, 2020)
As many as 27% of female adolescents in developing countries suffer from anemia. Anemia can have a big impact on the health of young women, especially pregnant women. The problem of anemia in adolescents needs to be overcome because teenagers will become pregnant women who of course need a healthy body more later. One effort is to take iron (Fe) supplements. This study aims to analyze the risk factors for attitudes and side effects of Fe tablets on the consumption of Fe tablets in female adolescents in high school. This study used a case-control study design. The population of this study was all young women who received Fe tablets at SMA Negeri 10 Kendari with a total of 85 students who were held from February 2020 to completion. The sample consisted of 40 people, namely 20 cases and 20 controls, the sampling technique was simple random sampling. The results showed that attitude is a risk factor for consuming Fe tablets, obtained OR = 6,000 (95% CI 1.458-24.686) and side effects of Fe tablets are a risk factor for consuming Fe tablets, the value of OR = 5.571 (95% CI 1.420-21.860) was obtained. It is necessary to increase communication, education, and information (IEC) in schoolchildren to increase positive attitudes and reduce the number of complaints of side effects of Fe tablets in school children.